Renovation and reconstruction of universities - Khanal, Sanjay N (Himalayan Journal of Sciences, 2006)
Society’s progress depends largely on the exploration and application of ideas. Worldwide, universities are the chief sources of these ideas. Lagging development is inevitably linked to poorly developed academic institutions. The problem is not just lack of adequate resources. Universities must be committed to the free exchange of ideas, tolerance of dissenting thought, incorporation of the widest possible range of disciplines, and a dedication to both personal growth and national service.Himalayan Journal of Sciences 1(2): 69, 2003The full text is available at the Himalayan Journal of Sciences website